2018
DOI: 10.1139/cjfas-2017-0026
|View full text |Cite
|
Sign up to set email alerts
|

Dry season survival of juvenile salmonids in an intermittent coastal stream

Abstract: We estimated dry season survival of imperiled salmonids in an intermittent coastal 25 stream in California across four years (2009)(2010)(2011)(2012). Our study encompassed two dry and two wet 26 winters allowing us to explore patterns of survival across and within dry seasons with different 27 antecedent precipitation. Apparent survival of age-0+ steelhead trout (Oncorhynchus mykiss) was 28 higher following wet winters compared to dry winters. Moreover, antecedent precipitation was 29 positively correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…Moreover, inter-annual variation in the over-summer survival of trout was related to both the magnitude and duration of summer low flows, providing a critical link between population dynamics and flow variability. Similarly, a recent study on O. mykiss in an intermittent California stream found that over-summer survival was positively correlated with cumulative precipitation of the previous winter [50]. In addition, in Mediterranean-climate California, Woelfle-Erskine et al [45] examined over-summer survival of imperiled juvenile coho salmon (O. kisutch) and steelhead trout and found that species-specific differences in juvenile distributions influenced the abiotic conditions that over-summering salmon and trout were exposed to, and hence the factors that governed over-summer survival.…”
Section: Fish Populationsmentioning
confidence: 74%
“…Moreover, inter-annual variation in the over-summer survival of trout was related to both the magnitude and duration of summer low flows, providing a critical link between population dynamics and flow variability. Similarly, a recent study on O. mykiss in an intermittent California stream found that over-summer survival was positively correlated with cumulative precipitation of the previous winter [50]. In addition, in Mediterranean-climate California, Woelfle-Erskine et al [45] examined over-summer survival of imperiled juvenile coho salmon (O. kisutch) and steelhead trout and found that species-specific differences in juvenile distributions influenced the abiotic conditions that over-summering salmon and trout were exposed to, and hence the factors that governed over-summer survival.…”
Section: Fish Populationsmentioning
confidence: 74%
“…Given the differences in total rainfall among years, we expected that fish growth would differ as well, especially considering that the period of summer that we monitored can be an especially harsh period for salmonids rearing in streams (Hwan et al. ). Regardless, we found little difference in growth rates among dry and very wet years.…”
Section: Discussionmentioning
confidence: 99%
“…, Hwan et al. ) and other arid and semi‐arid regions, such as parts of Oregon and Washington (Ebersole et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Status Review cited increasing negative impacts from climate change ) and noted that the greatest temperature shifts from climate change are expected in the summer. The movement of water from fogdrip through baseflow is critically important to coho in late summer when disconnected pools scattered along the stream can dry out (Woodward et al 2014;Hwan et al 2017;Woelfle-Erskine et al 2017). Juvenile coho in small pools are subject to high rates of mortality due to overheating, higher predation exposure, and reduced instream habitat (Sawaske 2014).…”
Section: Climate Change and The Recovery Planmentioning
confidence: 99%